The Lisbon Agreement on Femoroacetabular Impingement Imaging—part 1: overview - Mascarenhas, Vasco V.; Castro, Miguel O.; Rego, Paulo A.; Sutter, Reto; Sconfienza, Luca Maria; Kassarjian, Ara; Schmaranzer, Florian; Ayeni, Olufemi R.; Dietrich, Tobias Johannes; Robinson, Philip; Weber, Marc-André; Beaulé, Paul E.; et al. (European radiology, 2020)
Objectives Imaging assessment for the clinical management of femoroacetabular impingement (FAI) syndrome remains controversial because of a paucity of evidence-based guidance and notable variability in clinical practice, ultimately requiring expert consensus. The purpose of this agreement is to establish expert-based statements on FAI imaging, using formal techniques of consensus building. Methods A validated Delphi method and peer-reviewed literature were used to formally derive consensus among 30 panel members (21 musculoskeletal radiologists and 9 orthopaedic surgeons) from 13 countries. Forty-four questions were agreed on, and recent relevant seminal literature was circulated and classified in five major topics (‘General issues’, ‘Parameters and reporting’, ‘Radiographic assessment’, ‘MRI’ and ‘Ultrasound’) in order to produce answering statements. The level of evidence was noted for all statements, and panel members were asked to score their level of agreement with each statement (0 to 10) during iterative rounds. Either ‘consensus’, ‘agreement’ or ‘no agreement’ was achieved. Results Forty-seven statements were generated, and group consensus was reached for 45 (95.7%). Seventeen of these statements were selected as most important for dissemination in advance. There was no agreement for the two statements pertaining to ‘Ultrasound’. Conclusion Radiographic evaluation is the cornerstone of hip evaluation. An anteroposterior pelvis radiograph and a Dunn 45° view are recommended for the initial assessment of FAI although MRI with a dedicated protocol is the gold standard imaging technique in this setting. The resulting consensus can serve as a tool to reduce variability in clinical practices and guide further research for the clinical management of FAI. Key Points • FAI imaging literature is extensive although often of low level of evidence. • Radiographic evaluation with a reproducible technique is the cornerstone of hip imaging assessment. • MRI with a dedicated protocol is the gold standard imaging technique for FAI assessment.